THE EVICTION OF SHOPS ON THE RAILWAY ROAD AND THE ECONOMIC SUSTAINABILITY OF THE MERCHANT COMMUNITY IN SAMALANGA - Ulfa, Maya; Fakhrurrazi, Fakhrurrazi; Nazaruddin, M. (FISIP Universitas Malikussaleh, 2025)
This study examines the eviction of shops on the railway road and the economic sustainability of the trading community. The main focus in this study is the reason for the local government to evict the Samalanga market and how the community's economy is affected after the eviction of the Samalanga Market. This research was conducted in Samalanga District, Samalanga District, Bireuen Regency. The theory used to answer the problem in this study uses Max Weber's theory of social action. This study uses a descriptive qualitative method that aims to understand and describe the phenomena experienced by the research subjects. The data collection techniques used are using observation, interview, and documentation methods. The data analysis used in this research is data reduction, data presentation, and conclusion drawn. The results of the study show that the economic condition of the community was affected after the eviction of shops on the railway road in the Samalanga district: (a) unemployment increased in the merchant community after the eviction, (b) the merchant community lost their livelihood in meeting the needs of life, (c) the community felt disadvantaged after the loss of the trading stalls, (d) the change in income in the merchant community. The motive of the local government to evict shops on the Keude Samalanga railway road, Samalanga District, (a) the main factor of further infrastructure construction, (b) minimizing the occurrence of congestion, (c) complaints from the local community, (d) preventing the risk of traffic accidents, (e) the development of the existence of dayah in Samalanga District.